Phytochemical Profiling and Antioxidant Potential of Three Rhododendron Species Collected from Mustang District, Nepal - Khatri, Deepa; Poudel, Anisha; Ray, Minu Kumari; Gupta, Nimesh Kumar; Baral, Prakash; Kunwar, Sabina; Parajuli, Sabitri; Purja, Sarkesh; Adhikari, Shreekanta; Tripathi, Julu; Adhikari, Rupesh; Baruwal Chhetri, Sumit Bahadur; et al. (Himalayan Biodiversity, 2025)
Geographical and climatic variability significantly influence the chemical composition and biological activities of plant species. This study investigates and compares the extraction yield, phytochemical profiles, and antioxidant potential of three Rhododendron species namely R. arboreum (pink and red flower varieties), R. campanulatum, and R. anthopogon collected from Mustang district of Nepal. Among the species studied, R. campanulatum exhibited the highest extraction yield, whereas R. anthopogon yielded the lowest. Phytochemical screening revealed similar profiles between R. arboreum (pink and red flower varieties) and R. campanulatum, while R. anthopogon demonstrated comparatively lower phytochemical profiles. Antioxidant activity, assessed via the DPPH radical scavenging assay, indicated that R. arboreum (red flower) possessed the strongest free radical scavenging activity (IC₅₀ = 9.43 μg/mL), followed by R. campanulatum (IC₅₀ = 12.94 μg/mL), R. arboreum (pink flower) (IC₅₀ = 46.90 μg/mL), and R. anthopogon (IC₅₀ = 265.29 μg/mL). Variations in extraction yield, phytochemical composition, and antioxidant capacity compared to previously reported data may be attributed to differences in extraction techniques, solvents, plant parts analyzed, and the distinct environmental conditions of the Mustang region. Notably, the detection of proteins in the floral extracts of R. arboreum and R. campanulatum highlights their potential dual role as nutraceutical and phytotherapeutic resources.